PENERAPAN STRATEGI SQ4R DALAM MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN - Apri zan (Jurnal Muara Pendidikan, 2019)
Reading is one of skills which is crucial to be taught in the Elementary School. SQ4R (survey, question, read, reflect, and review) strategy is one of the alternatives that could be used to improve the students’ reading comprehension. The aim of this research was to describe the implementation of SQ4R strategy in improving the students’ reading comprehension skill in pre-reading, whilst-reading and post-reading in the fifth grade of SD Negeri 51/II Desa Paku Aji Kecamatan Tanah Sepenggal Lintas Kabupaten Bungo. This was a Classroom Action Research. The result of date analysis indicated that the use of SQ4R strategy could improve the students’ reading comprehension skill in pre-reading, whilst-reading and post-reading in the fifth grade of SD Negeri 51/II Desa Paku Aji.